Clinical Case of Surgical Correction of Infective Endocarditis of the Pulmonary Valve Associated with Infundibular Stenosis in an Adult - Roman Yo. Lekan; Volodymyr St. Moroz; Taras Vo. Romaniuk; Ivan Ro. Lekan; Lyudmyla Va. Balaban (Ukrainian Journal of Cardiovascular Surgery, 2025)
Background. Congenital heart defects, if not surgically corrected in a timely manner, are a predictor for the development of infective endocarditis, with the likelihood of its occurrence increasing with patient age.Aim. To present a comprehensive approach to the surgical management of infective endocarditis during complete correction of congenital heart disease.Case report. Patient M., 19 years old, was admitted to the Department of Cardiac Surgery of the Ternopil Regional Clinical Hospital (VKTOKL) on 30.12.2024 (case history No. 22656) with a diagnosis of infective endocarditis of the pulmonary artery valve (IEPAV), critical infundibular stenosis of the right ventricular outflow tract (RVOT), severe tricuspid valve (TV) insufficiency, circulatory failure of the III degree according to the New York Heart Association classification, concomitant bilateral infarct-pneumonia, and pulmonary failure of the II degree. On 03.01.2025, the patient underwent surgery, which included removal of vegetations, sanitation of the pulmonary artery valve, RVOT, and TV, resection of infundibular stenosis of the RVOT, prosthetic replacement of the pulmonary artery valve with a St. Jude Epic 23 bioprosthesis, and DeVega TV plasty under cardiopulmonary bypass. During the long-term follow-up, 4 months after surgery, the patient tolerated physical exertion well. Echocardiography revealed a gradient of 3 mm Hg in the RVOT, with no insufficiency of the TV or pulmonary artery valve, and a left ventricular ejection fraction (LVEF) of 65 %.Conclusions. Timely surgical correction of congenital heart defects with restoration of anatomical structures in the heart eliminates the cause-and-effect relationship leading to the development of infective endocarditis.The implantation of a biological valve into the pulmonary artery represents the optimal and definitive procedure for restoring hemodynamics in the pulmonary arterial system.